2018
DOI: 10.1002/cncr.31670
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the risk for aberrant opioid use behavior in patients receiving outpatient supportive care consultation at a comprehensive cancer center

Abstract: The current results indicate a high frequency of an elevated risk of ADB among patients with cancer. Men and patients who have anxiety, financial distress, and a prior history of alcoholism/illicit drug use are at increased risk of ADB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 36 publications
1
72
0
Order By: Relevance
“…It is an important distinction to make in such patients to enable safe prescribing and enhancing quality of life. In the USA, prevalence rates of drug misuse in patients with cancer range from 3% to 19%; however, population-level issues are considerably higher in the USA making it difficult to extrapolate 13–15…”
Section: Introductionmentioning
confidence: 99%
“…It is an important distinction to make in such patients to enable safe prescribing and enhancing quality of life. In the USA, prevalence rates of drug misuse in patients with cancer range from 3% to 19%; however, population-level issues are considerably higher in the USA making it difficult to extrapolate 13–15…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the odds for opioid use, and by extension pain medication use in general, and the level of symptoms of depression, general anxiety and catastrophizing suggests that it might be possible to decrease excessive opioid use by managing depressive symptoms better [48]. Moreover, it has been suggested that there might be a positive relationship between symptoms of depression [55,[141][142][143][144] and/or anxiety [55,141,142,144] and non-adherence to medication recommendations (e.g., pain medication dependence, overuse or taking someone else's prescription). Such non-adherence to medication recommendations is one of the causes of the opioid epidemic, indicating that it might be useful to target these CEF in clinical practice in an attempt to decrease medication misuse, withholding great potential for impacting upon the opioid epidemic.…”
Section: Discussion Of Confirmed Associationsmentioning
confidence: 99%
“…These findings underscore the importance of additional measures to reduce the risk of long-term opioid use. The use of validated screening tools in all patients using prescription opioids [34,35], and the targeting of psychosocial issues to combat 'chemical coping' [36,37] are examples of additional measures that may be used in conjunction with opioid-sparing approaches.…”
Section: Discussionmentioning
confidence: 99%